KARAKTERISASI SENYAWA AKTIF PADI LOKAL INDONESIA TAHAN TERHADAP CEKAMAN LINGKUNGAN - Tri Ratnasari; Wahyu Indra Duwi Fanata; Ummi Sholikhah; Ahmad Ilham Tanzil (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to characterize the active compounds in Indonesian local rice that are resistant to environmental stress in order to identify the nature of resistance to environmental stress, one of the indicators of which is the presence of flavonoid compounds. This step is one of the efforts that will lead to the acquisition of gene donors in the assembly of varieties resistant to biotic stress (pests and diseases) and abiotic stress (drought, high salinity, low temperature), which are very necessary in rice breeding programs. The method used is to plant 8 local rice varieties that are resistant to environmental stress in buckets in greenhouses. Next, analyze the content of active compounds by extracting the leaves and stems of rice plants, then macerate with methanol for 48 hours and test the content of active compounds. Then the total flavonoid content test was carried out using a quercetin standard and measured using a spectrophotometer. Whatever the results of this study, all samples showed active compounds containing flavonoids, alkaloids, tannins and saponins which were indicated by indicators of color change when tested with certain reagents. The results of the Flavonoid content analysis showed that the pendok variety had the highest flavonoid content, namely 3.9253 ± 0.06, and the Sigupai variety had the lowest flavonoid content, with a value of 1.8073 ± 0.07.